Desenvolvimento de métodos analíticos para determinação de Cd, Cu, Fe, Pb e Zn em amostras de patês por espectrometria de absorção atômica - Silveria Neves de Paula e Souza (2014)
The first chapter of this thesis includes the comparison of sensitivity, precision, limit of detection and limit of quantification of Flame Atomic Absorption Spectrometry - FAAS - operating in monoelementar and sequential modes. The determinations were performed by sequentially due to lower analysis time and lower sample consumption. In the sequence, is shown the development and validation of the method for determination of Cu, Fe, Mn and Zn in pâté samples. In the decomposition of pâté samples, three concentrations of HNO3 were evaluated: 3.5, 7.0 and 14 mol L-1 all at 30% H2O2 v v-1. For all samples the Mn concentration was below the quantification limit of the technique. The method employing HNO3 3.5 mol L-1 and 30% H2O2 v v-1 was adopted for the decomposition of the samples due to the security, generating less acid waste and obtaining lower values of analytical blank. In the validation step were evaluated the linearity, selectivity, precision, trueness, limits of detection and limits of quantification for Cu, Fe and Zn, at 95% confidence level. The limits of detection and the limits of quantification were 1.1 and 3.4 mg kg-1 for Cu, 2.1 and 6.8 mg kg-1 for Fe, 0.7 and 2.4 mg kg-1 for Zn, respectively. The second chapter includes the development and optimization of the sequential determination of Cd and Pb by TS-FF-AAS. Three atomizer tubes and four times of signals acquisition were evaluated with the aim of obtaining shorter intervals of delay time and eliminating memory effects. In the sequence, the figures of merit: linearity, precision, accuracy, limits of detection and limits of quantification were evaluated. The limits of detection and quantification were equal to 0.05 and 1.41 mg kg-1 for Cd, and 0.19 and 4.7 mg kg-1 for Pb. The use of carbon nanotubes (oxidized and unoxidized) was evaluated for the pre-concentration step of Cd and Pb. The interference from matrix constituents in the adsorption of DDTP Cd-complexes in the mini-column filled with carbon nanotubes was observed.